"The Impact of Content Marketing and Brand Impression on Purchase Intention in the Food and Beverage Industry: A Systematic Literature Review" - Firza Alifi, Zhorif (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
this paper aims at reviewing the literature on influence of content marketing and brand impression on purchase intention within the food and beverage sector. Marketing content has turned out to be crucial for the creation of content that is valuable useful, appropriate and consistent to consumers in an effort to attract them. At the same time, and of great relevance to the study, brand impression is a major factor in consumers’ association with a brand as well as their emotions towards the brand which in turn affects their purchase behaviour. This review assesses the direct and indirect impacts of content marketing on brand impression as gleaned from recent literature and how the two influences consumers purchase intention. Present research evidence indicates positive impacts of the concept, suggesting that effective content marketing also positively impacts the brand image, trust, engagement, perception and purchase intention. This research can serve as a useful reference for managers and manufacturers in the food and beverage industries implementing dynamic marketing methods to enhance their marketing capability to consumers in this ever-changing society.